A new Decapoda (Natantia, Malacostraca, Crustacea) from the Riachuelo formation (Albian), Sergipe basin - Reis, Márcia Aparecida Fernandes dos; Turbay, Caio Vinícius Gabrig; Cesero, Pedro De (Anuário do Instituto de Geociências, 2005)
A New Decapoda (Natantia, Malacostraca, Crustacea) From the Riachuelo Formation, Albian of the Sergipe Basin A "lobster" fossil from the Riachuelo Formation, Sergipe Sub-basin, is here described and placed in the Decapoda, Infraorder Palinura, based on the flattened carapace and the well-developed abdomen. The specimen is characterized by a dorsal median keel and a keel in each margin of the carapace and abdomen. Field data and petrographic studies suggest that the environment in which the Decapoda lived was probably a place with waves and moderate currents, located behind a sand barrier or in within a lagoon. Apparently, the carbonization process was responsible for specimen preservation.